A decade review of emergency obturator hernia repairs. Issue 7 (14th June 2021) - Diab, Jason; Badiani, Sarit; Berney, Christophe R.
Abstract: Background: Obturator hernia is a rare pelvic hernia associated with a high morbidity and mortality. It most commonly occurs in elderly, multiparous females with symptoms and signs of small bowel obstruction. We present an Australian hospital network experience on emergency presentations of obturator hernias highlighting differences between clinical profile and surgical management. Methods: A retrospective review of adult patients diagnosed with acute obturator hernia during a 10 year period (2010–2020) was conducted across 10 major Sydney hospitals in New South Wales, Australia. Results: Obturator hernia was diagnosed in 18 patients (mean 82.7 years, range: 60–96 years old), all confirmed on pre‐operative computed tomography imaging. The most common presentations were elderly women demonstrating clinical features of a small bowel obstruction. The mean onset of symptoms from home to hospital admission was 49.4 h. Non‐survivors had a significantly elevated urea level (15.6 vs. 7.8 mmol/L, p  = 0.036) at presentation and a longer delay from onset of presenting symptoms to diagnosis (84.0 vs. 36.2 h, p  = 0.028). Eleven patients underwent urgent laparotomy and six laparoscopic repairs. The mean operative time was 101.0 min. The average hospital length of stay was 16.2 days with a mortality rate of 27.8%. Conclusion: Timely diagnosis and operative intervention for obturator hernia is the cornerstone of management. Abstract : Obturator hernia is a rare pelvic hernia that most commonly occurs in elderly, multiparous females. Our study showed a mean onset of symptoms of 49.4 h with significant differences for urea and onset of symptoms from home to admission amongst survivors and non‐survivors. The average hospital length of stay was 16.2 days with a mortality rate of 27.8%.